2021
DOI: 10.1002/tox.23095
|View full text |Cite
|
Sign up to set email alerts
|

The impact of polystyrene microplastics on cardiomyocytes pyroptosis through NLRP3/Caspase‐1 signaling pathway and oxidative stress in Wistar rats

Abstract: The extensive existing of microplastics (MPs) in the ecosystem have increased considerable attention concerning their potential adverse effects, the toxicities and the underlying mechanism of MPs are still scarce. To explore the effect of MPs on cardiac tissue in Wistar rats and unravel the mechanism of pyroptosis and oxidative stress in the process of cardiomyocytes injury, 32 male Wister rats were divided into control group and three model groups, which were exposed to 0.5 mm PS MPs at 0.5, 5 and 50 mg/L for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 50 publications
2
48
0
Order By: Relevance
“…4 ), albeit it was beyond the capabilities of our study to confirm the increased secretion or activity of SOD3 enzyme in the extracellular milieu. This finding is also supported by previous studies that found oxidative stress induced by microplastic-mediated interference in mitochondrial function, suppression of cellular antioxidant systems, and increased generation of reactive oxygen species (Abidli et al 2021 ; An et al 2021 ; Chen et al 2021 ; Cortés et al 2020 ; Liu et al 2020 ; Wei et al 2021 ).
Fig.
…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…4 ), albeit it was beyond the capabilities of our study to confirm the increased secretion or activity of SOD3 enzyme in the extracellular milieu. This finding is also supported by previous studies that found oxidative stress induced by microplastic-mediated interference in mitochondrial function, suppression of cellular antioxidant systems, and increased generation of reactive oxygen species (Abidli et al 2021 ; An et al 2021 ; Chen et al 2021 ; Cortés et al 2020 ; Liu et al 2020 ; Wei et al 2021 ).
Fig.
…”
Section: Discussionsupporting
confidence: 86%
“…1 ). Previous research has shown the toxic effects of microplastics on cells and tissues, with effects such as DNA damage and mitochondrial dysfunction, and these underlying mechanisms, as well as activation of apoptotic pathways, may have contributed to the decreased cell viability observed here (Della Torre et al 2014 ; Estrela et al 2020 ; Li et al 2020d ; Wei et al 2021 ).…”
Section: Discussionmentioning
confidence: 66%
“…The detrimental effects of MP/NP exposure in aquatic species include embryotoxicity in zebrafish and sea urchins [7,8], hepatotoxicity in zebrafish, goldfish and tadpoles [9][10][11], growth inhibition of microalgae and fish larvae [12][13][14], decreased life spans of shrimp and plankton upon long-term exposure [12,15], deterioration of intestinal tissues in sea bass [16], and alterations in feeding behavior, metabolism and innate immunity in fish [17][18][19]. In terrestrial animals such as rodents, ingestion of MP/NP altered intestinal barrier function [20,21], gut microbiome [21][22][23], metabolism [20,24], behavior [25,26], innate immunity [23], reproduction [27,28] and cardiovascular function [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…By assessing effects in the GIT and the liver of mice exposed to PS MP via drinking water, liver toxicity, gut microbiota dysbiosis, disruption of the intestinal barrier and metabolic dysregulation have been demonstrated [166,167]. Oral exposure of rats to PS MPs has also provided evidence of translocation to the heart, resulting in cardiovascular dysfunction and fibrosis [185]. Regarding lung exposure, intratracheal instillation of PS NPs into the lungs of Sprague-Dawley rats has highlighted an influx of immune cells in a size-dependent fashion, with the smallest particles causing the greatest effect [164].…”
Section: Hazard Characterisationmentioning
confidence: 99%